HUBUNGAN KLASIFIKASI ANAK AUTIS BERDASARKAN CARS DENGAN TINGKAT KECEMASAN IBU 01 SLB AUTIS BINA ANGGITA - Maya Tika Sari; Moetrarsi Moetrarsi; Titik Kuntari (Faculty of Medicine, Universitas Islam Indonesia, 2009)
Autism had become a problem which is experienced by the family around the world, and autism happened on 5 among every 10.000 birth. Autism can be classified as light autism, medium autism and heavy autism. With having autism child, will give the anxiety to their parent especially the mother. The objectives of the research is to determine the relation between the autism children classifications based on CARS with the level of mother anxiety in autism SLB of Bina Anggita. This research is in <J nalytically non-experimental research with using cross-sectional method. Numbers of thesubjects used are 23 children with their mother from autism SLB of Bina Anggita. The data colleted with two ways, first direct observation to the autism children and the second filling the form of questionnaire by the mother. The analysis of the data used is fisher test. The classification of autism in Bina Anggita autism is generally as light autism to heavy autism (52,2%). The level af anxiety happened to the mostly mother are the light anxiety to medium anxiety 65,2%). There is no significant relation between the classification of autism child based on CARS with level of mother's anxiety (p=0,67).",